Age-dependent neurodegeneration and Alzheimer-amyloid plaque formation in transgenic Drosophila. - Greeve, I.; Kretzschmar, D.; Tschape, J.A.; Beyn, A.; Brellinger, C.; Schweizer, M.; Nitsch, R.M.; Reifegerste, R. (Journal of Neuroscience, 2004)
Beta-amyloid peptides that are cleaved from the amyloid precursor protein (APP) play a critical role in Alzheimer's disease (AD) pathophysiology. Here, we show that in Drosophila, the targeted expression of the key genes of AD, APP, the beta-site APP-cleaving enzyme BACE, and the presenilins led to the generation of beta-amyloid plaques and age-dependent neurodegeneration as well as to semilethality, a shortened life span, and defects in wing vein development. Genetic manipulations or pharmacological treatments with secretase inhibitors influenced the activity of the APP-processing proteases and modulated the severity of the phenotypes. This invertebrate model of amyloid plaque pathology demonstrates Abeta-induced neurodegeneration as a basic biological principle and may allow additional genetic analyses of the underlying molecular pathways.